Pengaruh Penerapan Metode Project Based Learning Terhadap Kreativitas Anak Usia 5-6 Tahun Pada Kurikulum Merdeka di TK Dharma Wanita - Kurniawati, Rina; Kristiana , Dian; ‘Azam Muttaqin, Muhammad (Generasi Emas, 2024)
Creativity is an essential skill that needs to be developed from an early age. Therefore, this study aims to determine the impact of the Project Based Learning method on the creativity of children aged 5-6 years in the Merdeka Curriculum at TK Dharma Wanita. This research employs a quantitative approach with a quasi-experimental design. The research design used is a pretest-posttest experiment with a control group. Data was analyzed using SPSS. Data collection was carried out through observation and children's creativity assessments. The results showed that the average creativity score of children in the experimental group (87.40) was significantly higher than that of the control group (77.60). This finding indicates that the implementation of the Project Based Learning method has a positive and significant effect on enhancing the creativity of children aged 5-6 years. This research aligns with the goals of the Merdeka Curriculum, which emphasizes the development of children's creativity and skills. The implication is that the Project Based Learning method can be considered an effective learning approach to boost early childhood creativity within the context of the Merdeka Curriculum.